Manus OnLine and the Text Encoding Initiative Schema - Giliola Barbero (OpenEdition, 2014)
The Italian Central Institute of Cataloguing (ICCU) has developed a web application to export manuscript descriptions from Manus OnLine (MOL), the Italian national catalogue of manuscripts, into TEI XML documents. As of June 2013, single descriptions can be downloaded from the MOL Online Public Access Catalogue (OPAC) as TEI XML documents by any user. The aim of the first tool is to supply manuscript descriptions to the institutions which produced them using MOL, because libraries and research organizations need to use their own data, outside the MOL project. The aim of the second service – exporting manuscript catalogues of entire collections as TEI XML files - is to promote exchange of data with other national and international projects. For these purposes, the ICCU needs a rich schema, not only a partial set of metadata, in order to be able to export complete structured manuscript descriptions. As bibliographical standards (MARC, Unimarc) cannot represent the entire structure of MOL descriptions adequately, ICCU adopted the TEI schema as an interchange standard. This paper describes solutions adopted by ICCU in encoding MOL contents within the TEI <msDesc> element and problems they encountered in performing this work. The encoding of information about material (<material>), number of folios and physical dimensions of manuscripts (<extent>) are discussed as well as a list of data pertaining to original letter cataloguing.